Family Nutrition: Parenting and Family Life - Larry Forthun (EDIS)
FCS-8869, a 6-page fact sheet by Larry Forthun, looks at three ways family can influence a child’s weight status: parental feeding practices and behavior, parenting style, and overall family functioning, and provides recommendations for improving family health and nutrition. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2008.